PENGARUH RISIKO BISNIS, KEBIJAKAN UTANG DAN KEBIJAKAN DIVIDEN TERHADAP KEPEMILIKAN MANAJERIAL PADA INDUSTRI MANUFAKTUR DI INDONESIA - Meliza Humaira, Nurhalis (Departemen Manajemen, 2018)
In a company of go public is often happened the conflict between of stockholder with the manager, this conflict can be reduce by managerial ownership, risk, debt, and dividend. The purpose of this study are examines and analyzes the effect of risk business, debt policy, and dividend policy to managerial ownership. Sample research as much 11 manufacturing companies in Indonesia during 2010 until 2015 period, taken with the method of purposive sampling which the company who owned the ownership of incoming managerial and made cash dividends consistantly during research period. The method analysis is using ordinary least square (OLS) with quadratic model and multiple linier by SPSS program. The results show that: (1) the variable of business risk has no non-linier influence on managerial ownership, the result show that business risk has no significant in positiveand negative impact on managerial ownership, but in linier regression, the influence between business risk and managerial ownershiphas no significantin positive effect (2) debt policy, which is expressed by debt to asset ratio (DAR) has a significant positive influence on managerial ownership, and (3) dividend policy, which is expressed by dividend payout ratio (DPR) has no significant negative influence on managerial ownership.